Literature Review and Treatment Approach with Commonly Used Ayurveda and Traditional Decoctions for Kampavata (Parkinson's Disease) - Hewageegana, H. G. S. P. (British Journal of Healthcare and Medical Research, 2024)
Kampavata is included in Vataja Nanatmaja Vikara (endogenous diseases caused by only one dosha), also known as Vepathuvata, explained by Acharya Charaka in Charaka Samhita, Sutrasthana, 20th chapter. It is a considerable problem in the ageing society because they face Dhatu kshaya conditions (body tissues are not neutralising properly, and as a result, Vata and Kapha dosha are gradually being vitiated). Samprapti of Kampavata develops with Srotorodha (Sanga) or by Dhatu kshaya inside the brain. Sometimes, family history causes the Kampavata disease. This study aims to assess the pharmacodynamic properties of commonly used herbal decoctions for Vata vyadhi, compelling individuals to adopt them to correct the pathology and alleviate the symptoms of the disease. Consequently, Maharasnadi Kashaya, Arkananthadi Kashaya, Punarnawa Kashaya, Dashamula Mruthairanda Kashaya, Brahmimundi Kashaya, Gandarvahasthadi Kashaya, Prasarinyadi Kashaya, Mashatmagupthadi Kashaya were identified as suitable decoctions to prescribe in the pathological conditions such as Srotorodha (Sanga) or Dhatu kshaya. Gandarvahasthadi Kashaya, Mashatmaguptadi Kahsaya, Maharasnadi Kashaya, Arkananthadi Kashaya, Punarnawa Kashaya, Dashamulamruthairanda Kashaya, Brahmimundi Kashaya and Prasarinvadi Kashaya can be used to reduce the symptoms such as Kampa (tremor), Sthambha (stiffness), Vag vikruti (Speech disorder) and night-time urination (nocturia) and Vit vibandhata (constipation). Accordingly, the most suitable decoctions can be applied to the sickness to get more positive results on a scientific basis through Ayurveda Chikitsa.